Role of Oxycodone Hydrochloride in Treating Radiotherapy-Related Pain - Yinxia Wang; Ligang Xing (Pain Research and Management)
Radiotherapy is commonly used to treat cancer patients. Besides the curable effect, radiotherapy also could relieve the pain of cancer patients. However, cancer pain is gradually alleviated about two weeks after radiotherapy. In addition, cancer patients who receive radiotherapy may also suffer from pain flare or radiotherapy-induced side effects such as radiation esophagitis, enteritis, and mucositis. Pain control is reported to be inadequate during the whole course of radiotherapy (before, during, and after radiotherapy), and quality of life is seriously affected. Hence, radiotherapy is suggested to be combined with analgesic drugs in clinical guidelines. Previous studies have shown that radiotherapy combined with oxycodone hydrochloride can effectively alleviate cancer pain. In this review, we firstly presented the necessity of analgesia during the whole course of radiotherapy. We also sketched the role of oxycodone hydrochloride in radiotherapy of bone metastases and radiotherapy-induced oral mucositis. Finally, we concluded that oxycodone hydrochloride shows good efficacy and tolerance and could be used for pain management before, during, and after radiotherapy.